Transcriptome analyses of rhesus monkey preimplantation embryos reveal a reduced capacity for DNA double-strand break repair in primate oocytes and early embryos - Wang, Xinyi; Liu, Denghui; He, Dajian; Suo, Shengbao; Xia, Xian; He, Xiechao; Han, Jing-Dong J.; Zheng, Ping (Genome Research, 2017)
Preimplantation embryogenesis encompasses several critical events including genome reprogramming, zygotic genome activation (ZGA), and cell-fate commitment. The molecular basis of these processes remains obscure in primates in which there is a high rate of embryo wastage. Thus, understanding the factors involved in genome reprogramming and ZGA might help reproductive success during this susceptible period of early development and generate induced pluripotent stem cells with greater efficiency. Moreover, explaining the molecular basis responsible for embryo wastage in primates will greatly expand our knowledge of species evolution. By using RNA-seq in single and pooled oocytes and embryos, we defined the transcriptome throughout preimplantation development in rhesus monkey. In comparison to archival human and mouse data, we found that the transcriptome dynamics of monkey oocytes and embryos were very similar to those of human but very different from those of mouse. We identified several classes of maternal and zygotic genes, whose expression peaks were highly correlated with the time frames of genome reprogramming, ZGA, and cell-fate commitment, respectively. Importantly, comparison of the ZGA-related network modules among the three species revealed less robust surveillance of genomic instability in primate oocytes and embryos than in rodents, particularly in the pathways of DNA damage signaling and homology-directed DNA double-strand break repair. This study highlights the utility of monkey models to better understand the molecular basis for genome reprogramming, ZGA, and genomic stability surveillance in human early embryogenesis and may provide insights for improved homologous recombination-mediated gene editing in monkey.
10.1101/gr.198044.115